1998
DOI: 10.1002/(sici)1097-4628(19981121)70:8<1567::aid-app14>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the dopant on the polypyrrole moisture content: Effects on conductivity and thermal stability

Abstract: Having in mind to produce electrically conductive carbon-epoxy composite materials, we have filled an insulating epoxy resin with an electronic conducting polymer, polypyrrole (PPy). To select the PPy that best suits this process, various PPys were chemically synthesized. The syntheses were performed in water via a dispersion polymerization route using, initially, either FeCl 3 (PPy-Cl Ϫ ) or (NH 4 ) 2 S 2 O 8 (PPy-HSO 4Ϫ ) as oxidizing agents. Then, using (NH 4 ) 2 S 2 O 8 as the oxidant, two other PPy doped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…According to Sasso et al, 43 the decomposition of oxidant tends to produce ions that could act as dopant during chemical PPy polymerization. For instance, when oxidants such as FeCl 3 and APS are used in the synthesis, they form chloride (Cl − and ClO 4 − ) and sulfate (SO 4 − ) ions 43,131,132 …”
Section: Factors Affecting Ppy Conductivitymentioning
confidence: 99%
“…According to Sasso et al, 43 the decomposition of oxidant tends to produce ions that could act as dopant during chemical PPy polymerization. For instance, when oxidants such as FeCl 3 and APS are used in the synthesis, they form chloride (Cl − and ClO 4 − ) and sulfate (SO 4 − ) ions 43,131,132 …”
Section: Factors Affecting Ppy Conductivitymentioning
confidence: 99%
“…New aromatic nitrogenenous polymers are continuously emerging due to their versatility, easy preparation, and very attractive property-cost performance including much higher gas separation ability than any other polymer. 1 The most widely studied conducting polymers are poly(aniline), [2][3][4][5][6][7][8][9][10][11][12] poly(pyrrole), [13][14][15][16][17][18][19][20] poly(thiophenes), [21][22][23][24][25][26] and poly(carbazole). [27][28][29][30][31][32][33] The carbazole (CZ) homopolymers have potential applications in the field of optoelectronics because of their interesting blue luminescence due to their limited p-conjugation.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it is also believed that the chemical process can help improve the interfacial bonding between the graphite nanoplatelets (GNPs) and polymer matrix, which also increased the κ values of the nanocomposites [96]. As reported by C. Cassignol et al, the κ values of polypyrrole (PPy) increased with the moisture content, especially from 8.5% to 13.5% [98]. Tomko et al reported that the hydrated tandem-repeat (TR) protein films had an increased thermal conductivity compared to ambient state TR protein films [13].…”
Section: Parameters To Influence the Thermal Conductivity Of Protementioning
confidence: 99%
“…Tomko et al reported that the hydrated tandem-repeat (TR) protein films had an increased thermal conductivity compared to ambient state TR protein films [13]. Therefore, in addition to parameters such as crystallinity, chain orientation and fillers, the κ values of polymers also vary with the change of temperature, moisture and other factors [57,98,99]. Due to the anisotropic structure and microstructure of polymers, the κ values of polymer in the cross-plane direction or the in-plane direction can also be different [100,101,102,103,104].…”
Section: Parameters To Influence the Thermal Conductivity Of Protementioning
confidence: 99%